2013
DOI: 10.1111/efp.12078
|View full text |Cite
|
Sign up to set email alerts
|

The development of a species‐specific test to detect Hymenoschyphus pseudoalbidus in ash tissues

Abstract: Ash dieback, caused by the pathogen Hymenoscyphus pseudoalbidus, is an emerging lethal disease of Fraxinus excelsior in large parts of Europe. To develop a method for the early detection of H. pseudoalbidus, we designed primers for 46 microsatellites (simple sequence repeats, SSRs) of the pathogen. Seven pairs of primers (SSR38, SSR58, SSR114, SSR198, SSR206, SSR211 and SSR212) were found to bind only to the genome of H. pseudoalbidus, but not to the genome of H. albidus or to 52 different fungal endophytes is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In the Ukraine, this fungus was detected in litter, in ash petioles from the previous year (Davydenko et al 2013). It was also detected in ash wood in Slovenia (Gherghel et al 2014) and in the bark and buds of living ash branches in New Zealand (Chen 2012). The present results suggest that its frequency increases in stems and twigs with advanced necrosis, which categorizes the fungus rather as a secondary invader or saprotroph.…”
Section: Occurrence Of Other Frequent Fungal Speciesmentioning
confidence: 98%
“…In the Ukraine, this fungus was detected in litter, in ash petioles from the previous year (Davydenko et al 2013). It was also detected in ash wood in Slovenia (Gherghel et al 2014) and in the bark and buds of living ash branches in New Zealand (Chen 2012). The present results suggest that its frequency increases in stems and twigs with advanced necrosis, which categorizes the fungus rather as a secondary invader or saprotroph.…”
Section: Occurrence Of Other Frequent Fungal Speciesmentioning
confidence: 98%
“…Not only the screening for candidates is important but also the characterization of the underlying resistance mechanisms, to evaluate which genetic material can be utilized for further breeding [9] and to prove the robustness of the observed partial resistance when new virulent strains evolve. Also in south-eastern Germany [25] and other countries, a high level of fungal genetic variation was already found [34] and the virulence of the different strains has to be proven in the future. The survival of potentially resistant trees is endangered not only by the infections with new evolving virulent strains of H. fraxineus itself, but also by secondary pathogens, like the ash bark beetles or other species of Armillaria that can be increasingly found in weakened ash stands as it was proven in this study.…”
Section: Discussionmentioning
confidence: 99%
“…From a total of 74 trees, 40 successful isolations on malt agar supplemented with antibiotic (20 g¨L´1 malt extract, 100 mg¨L´1 streptomycin and 15 g¨L´1 agar) were performed. In earlier studies, the presence of the fungus was also confirmed by PCR analysis for six study sites [25]. In each pole stand, except for Freising, one tree was felled and samples from three symptomatic branches were used for DNA extraction.…”
Section: Isolation and Cultivation Of H Fraxineus From Infected Branmentioning
confidence: 92%
See 1 more Smart Citation
“…This is important for breeding programs to ensure a wide genetic base, particularly since analyses based on microsatellites revealed genetic variation in H. fraxineus populations (BENGTSSON et al, 2012;FUSSI et al, 2012;GHERGHEL et al, 2013) and genotype dependent differences in the pathogen -tree interaction might be expected.…”
Section: Genetic Differences Between Susceptible and Less Susceptiblementioning
confidence: 99%